Phytochemical Screening and Evaluation of the Anxiolytic and Cytotoxic Potential of the Leaves and Stem of Ocimum basilicum Linn. var. pilosum (Willd.) Benth. (Chittagong University Journal of Biological Sciences, 2024)
This research investigated the qualitative screening of phytochemicals, anxiolytic and cytotoxic potentials of crude methanol extracts of the leaves (MEL) and stem (MES) of Ocimum basilicum Linn. var. pilosum (Willd.) Benth is a new variant of sweet basil herb. For the solvent extraction process, methanol was selected due to its ability to solubilize both polar and non-polar plant constituents. Phytochemical analysis was carried out by using the established methods. The anxiolytic activity was assessed on Swiss albino mice using the hole board apparatus, and cytotoxicity was measured using the brine shrimp lethality assay. The current results showed that MEL and MES contained several active secondary metabolites, including alkaloids, glycosides, flavonoids, phenols, tannins, triterpenes, and resins. MEL (200, 400 mg/kg) and MES (400 mg/kg) were found to be significantly (P < 0.001) effective anxiolytic agents as compared to the negative control group. In the case of cytotoxicity activity, MEL showed an LC50 value of 244.45 µg/ml (standard 0.16 µg/ml), indicating cytotoxic potential compared to the negative control. Thus, the findings revealed that MEL and MES were excellent anxiolytic agents with a moderate cytotoxic potential.Chittagong Univ. J. B. Sci. Vol. 12 (1 & 2): 27-34, 2024